Utilization of Information and Communication Technology (ICT) in Learning in Indonesia: Penggunaan Teknologi Informasi dan Komunikasi (TIK) dalam Pembelajaran di Indonesia - Qonita Izza (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Abstrak. : The rapid development of information and communication technology (ICT) has driven changes in education. Advancing information technology improves performance and enables activities to be carried out quickly and accurately. According to Supianti (2018), life now involves various electronic needs like e-government, e-commerce, e-education, e-medicine, and e-laboratory. In Indonesia, ICT use in education is rising to enhance learning quality and access. ICT offers benefits such as educational software, e-learning, and multimedia tools that make learning more engaging and interactive. However, challenges like unequal internet access and insufficient technological devices remain. ICT improves how teachers deliver materials and interact with students, making learning more engaging and motivating (Setiawan, 2020). Adequate infrastructure and improved teacher competencies are needed to optimize these benefits. Many teachers need further training to use ICT effectively (Puspitasari, 2017). This study explores ICT use in Indonesian education, identifies challenges, and seeks solutions. Using a qualitative approach, it analyzes literature and surveys from teachers in major Indonesian cities, combining data from recent academic sources to understand ICT's impact on education.